PENDAMPINGAN PEMBUATAN BRANDING DAN LABEL PRODUK LOKAL DUSUN KEMPUL UNTUK MENINGKATKAN DAYA SAING - Musarofah, Unun; Purwanto (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
Brand identity gaps are a crucial obstacle for rural MSMEs in achieving competitiveness in a competitive market. This community service aims to assist three MSMEs in Kempul Hamlet (Arsaka Food, Kemplang Mbok Ru, and Geblek Mak Yah) in formulating visual identities through the creation of standardized logo designs and product labels. The method used is Participatory Action Research (PAR) through cycles of inquiry, action, reflection, and evaluation. The novelty of this service lies in combining visual aesthetics with food regulation compliance, where the resulting labels include mandatory elements such as product name, ingredients, expiration date, and production codes. The results show that the three partners successfully obtained representative brand identities and informative packaging labels. Through the inquiry and reflection process, the designs reflect the local philosophy of the entrepreneurs, fostering a strong sense of ownership. This output is proven to enhance the product's professional image and expand the market reach potential for partners beyond the Kempul Hamlet area.